Knowing and decorating the world: illustrations and textual descriptions in the maps of the fourth edition of the Mercator-Hondius Atlas (1613) - Skurnik, Johanna; Latva, Otto (Approaching Religion, 2016)
This article analyses the Mercator-Hondius Atlas maps in the context of constructing knowledge of the world. In what follows, we analyse the elements of continental geographies and ocean spaces on the maps presented in the atlas. We take as our starting point the tension between empirical and theoretical knowledge and examine the changes occurring in the ways of representing land and sea on atlas maps which are evident in the Mercator-Hondius Atlas. Consequently, we investigate how the world was represented through information in pictorial and textual form. We argue that the maps in the Mercator-Hondius Atlas make explicit not only the multiple cartographical traditions and the layered nature of atlases as artefacts. They also exemplify the various coexisting functions of the atlas.